Asosiasi Lokus Mikrosatelit BMS1282 dengan Kejadian Kawin Berulang pada Sapi Bali - Dewi, Yesy Febnica; Wandia, I Nengah; Puja, I Ketut (Veterinary Science and Medicine Journal, 2014)
Bali cattle has an important role to fulfill the meat demands in Indonesia. The improvement of molecular technology will facilitated bali cattle genomic selection. The aim of this research was to verify association between BMS1282 microsatellite locus and repeat breeding in bali cattle. Totalling 52 bali cattle blood samples was taken from UD Sari Laba, Bangli, Bali as DNA resources. DNA was extracted using blood mini Kit qiagen and microsatellite locus was amplified by Polymerase Chain Reaction (PCR). Alleles were separated with 6% PAGE and visualized using silver stain. There were 5 alleles in BMS1282 locus which the alleles size varied from 148 to 156 bp. Allele 152 was the higest frequency (54.81%) and allele 156 was the lowest frequency (1.92%). The value of heterozygosity (Ho), He, and PIC was 0.346, 0.626, and 0.569. consecutively. Statistical analysis revealed that BMS1282 locus has no assosiation with the repeat breeding (P>0.05). This result indicates that BMS 1282 locus has no important role in regulating the repeat breeding.
Keywords: Bali catlle; repeat breeding; microsatellite BMS1282; heterozigosity